Internal Limiting Membrane (ILM) Peeling for Macular Edema Secondary to Branch Retinal Vein Occlusion (BRVO): Doi: 10.36351/pjo.v37i1.1144 - Khaqan, Hussain Ahmad; Imtiaz, Usman; Baksh, Hasnain Muhammad; Ur Rehman, Hafiz Ateeq; Naz, Raheela (Pakistan Journal of Ophthalmology, 2020)
Purpose: To find out the anatomic and functional outcomes of pars plana vitrectomy (PPV) and internal limiting membrane (ILM) peeling in patients with refractory macular edema associated with branch retinal vein occlusion (BRVO). Study Design: Interventional case series. Place and Duration of Study: Ophthalmology department at Lahore General Hospital, Lahore from 2015 to 2019. Methods: Fifty-five eyes of patients presenting with refractory macular edema associated with branch retinal vein occlusion (BRVO) were recruited for this study. They were treated using 23-gauge pars plana vitrectomy and Brilliant Blue Green assisted internal limiting membrane peeling. Pre-operative and post-operative best-corrected visual acuity (BCVA) and macular edema were assessed by fluorescein angiography and optical coherence tomography (OCT). Monthly follow up was continued for one year. Results: In 46 (83.6%) eyes, central macular thickness improved from 465 ± 91 µm at baseline to 295 ± 103 µm post-operatively, (P < 0.003) at one year of followup. In nine (16.3%) eyes, there was no improvement in central macular thickness. Improvement in best-corrected visual acuity (BCVA) was seen in 43 (78.1%) eyes. Out of these 43 eyes, 37 (86%) eyes had mean 3 Snellen lines improvement while six (13.9%) eyes had 2.4 Snellen lines improvement. In 12 eyes (21.8%) BCVA did not improve. No statistically significant difference was seen in post-operative BCVA between ischemic and non-ischemic BRVO (p > 0.05). Conclusion: Twenty-three gauge vitrectomy with Brilliant Blue Green (BBG) assisted ILM peeling is effective in reducing refractory macular edema and improves visual acuity in ischemic and non-ischemic BRVO. Key Words: Internal limiting membrane, Macular edema, Retinal vein occlusion, Brilliant Blue Green.